2018
DOI: 10.2147/iprp.s163968
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review on do’s and don’ts in prescription label writing – lessons for pharmacists

Abstract: Providing medicines information is a key role of a pharmacist. Miscommunication between pharmacist and patient may lead to adverse drug events or therapeutic failure. The aim of the review was to summarize the available research findings on factors that lead to poor communication between pharmacist and patient when providing written medicines information on dispensing and auxiliary labels and identify successful interventional approaches that help to alleviate these concerns. We selected articles available on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…What is yet unknown, is how specific textual elements in DLIs (e.g., the presentation of numbers, or use of medical jargon) and patients’ health literacy skills are related to (improved) comprehension of DLIs. While Samaranayake et al [ 31 ] conducted a narrative review on the impact of patient-related factors, such as age and health literacy, and drug label-related factors, such as the use of icons and the format of the label, on the comprehensibility of DLIs, they did not provide an overview of specific textual elements associated with better comprehension of DLIs. Knowledge of which textual elements facilitates patients’ comprehension of DLIs, especially those with limited health literacy, will provide concrete directions for health professionals, such as physicians and pharmacists, on how to optimize their drug prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…What is yet unknown, is how specific textual elements in DLIs (e.g., the presentation of numbers, or use of medical jargon) and patients’ health literacy skills are related to (improved) comprehension of DLIs. While Samaranayake et al [ 31 ] conducted a narrative review on the impact of patient-related factors, such as age and health literacy, and drug label-related factors, such as the use of icons and the format of the label, on the comprehensibility of DLIs, they did not provide an overview of specific textual elements associated with better comprehension of DLIs. Knowledge of which textual elements facilitates patients’ comprehension of DLIs, especially those with limited health literacy, will provide concrete directions for health professionals, such as physicians and pharmacists, on how to optimize their drug prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…It can be said that most of the pharmacists agreed that the unawareness of the caretaker may result in medication errors at home. Poor comprehension to medication instructions in such elderly patients may find it difficult to read, understand or even recall the information provided may also lead to medication errors (Samaranayake et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“… 11 On the other hand, PMLs provided by the health system may use complex or unfamiliar terms, unclear instructions, poorly organized information and have poor legibility, contributing to poor understanding. 1 , 2 , 9 , 10 , 12 , 13 Older adults rely heavily on PMLs due to higher prevalence of chronic disease 14 and medication intake. 15 Therefore, PMLs should accommodate the needs of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…While published reviews on best practices for designing PMLs 12 , 16 , 17 , 18 and international labelling guidelines 19 , 20 are available, health systems have yet to incorporate many of these evidence-based improvements to their PMLs. Studies comparing actual PMLs' print characteristics against labelling guidelines have found non-conformity to format and content recommendations.…”
Section: Introductionmentioning
confidence: 99%